PLS-SEM Method in Analyzing Student Satisfaction at Universitas Sumatera Utara Towards SATU USU Services - Manik, Yessi Mardina; Manurung, Asima; Siringoringo, Yan Batara Putra; Yanti, Maulida; Br Tarigan, Enita Dewi (Prodi Pendidikan Matematika FKIP Universitas HKBP Nommensen, 2025)
SATU USU is a platform that integrates various digital services at USU into a single portal, simplifying students’ access to academic and administrative information. The purpose of this study is to analyze student satisfaction with the SATU USU service and to identify which factors have a significantly influence. This research employs a quantitative approach, with data collected through a questionnaire distributed via Google Forms. A modified WebQual 4.0 model was used to measure service quality, and data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The analysis results show an R² value of 0.817, indicating that the variables in the research model explain 81.7% of the variance in student satisfaction. Furthermore, the analysis reveals that the variables of usability, service interaction quality, and trust have a significant impact on student satisfaction, while the information quality variable does not show a significant effect in the use of SATU USU.